Static and dynamic causes of the decline in the price of mobile telecommunication services - François Jeanjean Orange (International Telecommunications Society (ITS), 2013)
Telecommunication industry is characterized by a sharp fall in unit price which highly benefits to consumers. This article aims to identify the main parameters that lead to such a fall. Using a 13-countries wireless market dataset, it shows that investment actually drives the exponential growth of traffic. As the growth of revenues are much lower, the price of MByte decreases sharply.Telecom operators need some margin to invest. The increased margin increases subscription price, however, in the same time, it also increases investment. The paper shows that the impact on investment highly outweighs the impact on subscription price. As a result, the overall impact of increased margin is the fall of Mbyte price.
Keywords: 330